FTIR (Fourier Transform Infrared) Spectroscopy Method for Bacillus cereus Characterization - Silfiani, Intan; Abadi, Abdul Latief; Aini, Luqman Qurata; Prillianti, Kestrillia Rega; Prabowo, Matheus Randy; Dianti, Sylvia Herli (Research Journal of Life Science, 2022)
One of the potentials of Bacillus cereus bacteria is as an inducer of systemic resistance in plants against plant diseases. FTIR spectroscopy is a traditional method extensively utilized in the pharmaceutical industry, since it is fast, non-destructive, and requires minimal sample preparation. In this study, the indicators that were effectively discovered were the functional groups that compose carbohydrates and lipids. The absorption region to be analyzed for the functional groups that compose carbohydrates is in the wavenumber region of 1200-800 cm-1, whereas the functional groups that compose up lipids are in the wavenumber range of 3020-2800 cm-1 and 1800-800 cm-1. The signal produced on the spectral signature of B. cereus isolates revealing the functional groups that compose carbohydrates is at the absorption values of 1185, 1132, 1122, 1098, 1078, 1056, 1010, and 973 cm-1. This is analogous to the notion that the cell wall of B. cereus is composed of peptidoglycan which contains carbohydrates. While the absorption values that indicate the functional groups that make up lipids are 2969, 2955, 2925, 2870, 2846, 1759, 1733, 1471, 1455, 1234, 895 cm-1, which according to the literature suggests that the body structure of B. cereus contains 2-3% of the dry weight of bacterial cells and consists of neutral lipids and phospholipids.